IN VITRO ANTIMICROBIAL ACTIVITY OF Lactobacillus parabuchneri NU14 AS A PROBIOTIC - Nouralhuda A. Hussein,; Khalid J. K. Luti, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The present study was designed to select a suitable isolate of Lactobacillus sp. in order to use it as a probiotic in a toothpaste for the prevention of dental disease. For this purpose, 30 Lactobacillus isolates were collected from different sources and subjected to a screening program to evaluate their antagonism activities against three oral pathogens: Staphylococcus aureus, E. coli and Streptococcus mutans. Eight Lactobacillus isolates were selected from primary screening according to their ability to inhibit the growth of three indicators which then exposed to a secondary screening to detect their ability to produce high amount of bacteriocin. Based on results, the isolate Lactobacillus parabuchneri.Nu14 was selected as a highest bacteriocin producing isolate. Next, several tests were performed to study the properties of Lactobacillus parabuchneri Nu14, in particular its biosafety and its suitability to be a successful probiotic. Results showed that Lactobacillus parabuchneri was resistance to β-lactams group such as penicillin and ampicillin whereas, it was sensitive to amoxicillin-clavulanate. In addition, results revealed that this bacterium was strongly adherent and good biofilm producer, has the ability to survive in pH 2 for 2hr; has the ability of surviving in the presence of 85.2% of lysozyme after 90 min; tolerant to 0.3% of bile salts for 2hr; had high auto-aggregation capability and high ability of adhering with S. mutans. Two toothpaste formulas were selected and optimized to choose the most useful one that can be used in this study. Based on results, L. parabuchneri Nu14 was successfully survive in formula II over 21 days.